PENGARUH BRAND LEADERSHIP DAN BRAND TRUST TERHADAP REPURCHASE INTENTION KONSUMEN PRODUK MAKANAN DI TOKOPEDIA - Yohanna Nathania; Marcellia Susan (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2023)
The digital industry is growing rapidly until it can easily meet the community's needs. Especially since the COVID-19 pandemic, which has been going on since early 2020 in Indonesia, has forced people to use technology to meet their daily needs, one of which is the use of the Tokopedia application to buy food products. The purpose of this study was to analyze the effect of brand leadership and brand trust on repurchase intentions by active users of Tokopedia with a sample of 108 respondents. In distributing the questionnaire using a Likert scale and using PLS. Based on the examination of the data, there is a positive influence of brand leadership on repurchase intentions and a positive influence of brand trust on repurchase intentions. This research can provide information about the dimensions that Tokopedia can improve to strengthen each variable in the future. This research has limitations and recommendations for future researchers to produce better research.